1990
DOI: 10.1104/pp.92.4.1062
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Induced Changes in the Fatty Acid Composition of the Cyanobacterium, Synechocystis PCC6803

Abstract: Changes in glycerolipid and fatty acid composition with a change in growth temperature were studied in the cyanobacterium, Synechocystis PCC6803. Under isothermal growth conditions, temperature did not significantly affect the composition of the various classes of lipids, but a decrease in temperature altered the degree of unsaturation of Cie acids at the sn-1 position, but not that of C16 acids at the sn-2 position of the glycerol moiety in each class of lipids. When the growth temperature was shifted from 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
127
1
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(141 citation statements)
references
References 29 publications
12
127
1
1
Order By: Relevance
“…The drastic decrease observed in state transitions amplitude during cold shock for the tropical and mid-latitude strains generally arose before the PBS uncoupling in these strains, indicating that the decline in state transition during the first few days was not directly related to PBS dismantling (Figures 2b and 3a). These early perturbations of the state transition process might originate in the cold-induced changes in the fluidity of the thylakoidal membranes, as low temperature is well known to induce membrane stiffening (Wada and Murata, 1990;Murata and Los, 1997;Mikami and Murata, 2003). Later during the cold period, PBS dismantling likely contributed to the complete inhibition of state transitions.…”
Section: Discussionmentioning
confidence: 99%
“…The drastic decrease observed in state transitions amplitude during cold shock for the tropical and mid-latitude strains generally arose before the PBS uncoupling in these strains, indicating that the decline in state transition during the first few days was not directly related to PBS dismantling (Figures 2b and 3a). These early perturbations of the state transition process might originate in the cold-induced changes in the fluidity of the thylakoidal membranes, as low temperature is well known to induce membrane stiffening (Wada and Murata, 1990;Murata and Los, 1997;Mikami and Murata, 2003). Later during the cold period, PBS dismantling likely contributed to the complete inhibition of state transitions.…”
Section: Discussionmentioning
confidence: 99%
“…Two genes downregulated in the wild-type, desA (slr1350) and desD (sll0262), encode acyl-lipid desaturases that introduce double bonds at defined positions in fatty acids that form membrane glycerolipids (Wada & Murata, 1990). The presence of double bonds in membrane lipids has been implicated in protecting PSII from photoinhibiton under stress conditions (Allakhverdiev et al, 2001;Tasaka et al, 1996).…”
Section: The Absence Of Hik31 Alters Transcriptional Response To Low mentioning
confidence: 99%
“…These results suggested that ω-3 Des, which converts LA to ALA, is regulated by temperature. Whereas cold-induced expression of ω-3 Des gene at mRNA level have been found in algae and many plants (Wada and Murata 1990;Shi et al, 2011;Zhang et al, Science Publications AJBB 2011; Takemura et al, 2012) and it is most sensitive to changes in temperature compared to other desaturases such as ∆9, ∆12 and ∆6 Des gene (Sakamoto et al, 1994). Therefore, it is suggested that ω-3 Des gene in Mt.…”
Section: Molecular Switch Of Microorganisms That Produce N-6 Fatty Acmentioning
confidence: 99%
“…This regulation of PUFA metabolic flux is partly due to the substrate specificity of the ∆6 Des Table 2, Sakuradani and Shimizu, 2003;Sakuradani et al, 2005;Zhu et al, 2002) which prefers n-6 fatty acid LA to n-3 ALA as substrate and its ω-3 Des must be repressed at physiological growth temperature (Shimizu et al, 1998). Although the ω-3 Des have been cloned and biochemically studied in a few microorganisms Table 5, (Gellerman and Schlenk, 1979;Pereira et al, 2004;Sakamoto et al, 1994;Wada and Murata, 1990), its expression level in oleaginous microorganisms has not been determined so far. However over-expression of ω-3 Des in Mt.…”
Section: Molecular Switch Of Microorganisms That Produce N-6 Fatty Acmentioning
confidence: 99%
See 1 more Smart Citation